2020
DOI: 10.1155/2020/6563520
|View full text |Cite
|
Sign up to set email alerts
|

Numerical Simulation of Conical Pick Cutting Arc Rock Plate Fracture Based on ANSYS/LS‐DYNA

Abstract: The new method of rock breaking based on the combination of circular sawblade and conical pick was proposed to improve the effectiveness of hard rock breaking. The numerical simulation method was applied to research the conical pick cutting arc rock plate by ANSYS/LS-DYNA. The conical pick cutting arc rock plate numerical simulation model was established to research the influence of arc rock plate structural parameters and cutting parameters on cracks formation and propagation of the arc rock plate and the cut… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 63 publications
(3 citation statements)
references
References 21 publications
0
3
0
Order By: Relevance
“…The model was initially applied to concrete materials, and it has been shown that it has good applicability in the field of rock materials. It can be seen from the site geological survey that the site is basically complete and relatively complete limestone, and the relevant model parameters [27] are shown in Table 3 In Table 3 ρ denotes the density of rock; g represents the shear modulus of rock; f c means quasi-static uniaxial compressive strength; A, B, N and S max show the limit surface parameters, where A represents the characteristic viscous strength index, B represents the characteristic pressure hardening coefficient, N represents the pressure hardening index, and S max represents the maximum characteristic equivalent stress that the material can achieve. C represents the strain rate influence parameter; D 1 and D 2 indicate damage constants.…”
Section: Numerical Model 31 Model Parametersmentioning
confidence: 99%
“…The model was initially applied to concrete materials, and it has been shown that it has good applicability in the field of rock materials. It can be seen from the site geological survey that the site is basically complete and relatively complete limestone, and the relevant model parameters [27] are shown in Table 3 In Table 3 ρ denotes the density of rock; g represents the shear modulus of rock; f c means quasi-static uniaxial compressive strength; A, B, N and S max show the limit surface parameters, where A represents the characteristic viscous strength index, B represents the characteristic pressure hardening coefficient, N represents the pressure hardening index, and S max represents the maximum characteristic equivalent stress that the material can achieve. C represents the strain rate influence parameter; D 1 and D 2 indicate damage constants.…”
Section: Numerical Model 31 Model Parametersmentioning
confidence: 99%
“…Besides, numerical simulation tests are often widely applied in studying the failure process of rock mass. Simulators such as ABAQUS, ANSYS, FLAC3D and CASRock regard rock mass as a continuous medium, and the finite element method, finite difference method, cellular automata were used in the discretization equation and simulate the expansion process of static and dynamic cracks in rock mass [26][27][28][29]. Discrete element methods, without specifying complex crack initiation criteria, regard a rock mass as a discontinuous discrete medium and have been widely applied in simulating crack propagation and failure analysis of rock masses [30].…”
Section: Introductionmentioning
confidence: 99%
“…Lu et al [20][21][22][23][24] proposed a combined cutting method of saw blade-pick and studied the cutting force of rock under different conditions. Wang et al 25,26 researched the effects of the cutting parameters of diamond sawblades on cutting rock and investigated the relationship between cutting force and cutting parameters of the conical pick in the rock cutting process.…”
Section: Introductionmentioning
confidence: 99%